Cabo Verde Economic Update, April 2021 : Rebounding from the Crisis - Restoring Fiscal Sustainability and Leveraging the Private Sector for a more Resilient and Sustainable Recovery - World Bank (World Bank, Washington, DC, 2021)
The objective of this report is to provide an update to the Government of Cabo Verde, think-tanks and researchers, and the public on the state of the Cabo Verde economy and its outlook, together with the structural reforms required to strengthen the foundations for private sector-led recovery from the COVID-19 crises. The report begins with a chapter on recent economic developments, the medium-term outlook, and risks. It includes sections on growth, fiscal policy, public debt, the external sector, monetary developments, and inflation. The second chapter stresses the importance of improving the investment climate to leverage the role of the private sector for an inclusive economic recovery. It provides an overview of key challenges and actionable policy priorities around foreign direct investment, the business environment, and competition.